Peran, Fungsi, dan Pengakuan UNESCO dalam MOW Kepada Indonesia Tentang Naskah Negarakertagama sebagai Memori Kolektif - Setiawan, Sania Aqila; Deni, Fitra (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
The Negarakertagama manuscript is a historic manuscript that must be preserved since it contains information from the Majapahit Kingdom's era. The problem arose are the threat of the manuscript not to be claimed by other nations, the threat losing documentary heritage due to war and the threat of geographical factors in Indonesia. The aim of the research is analysing the role, function, and recognition of UNESCO to protect the manuscript belongs to Indonesia in the memory of the world program. The research methodologies applied are qualitative (data collection techniques includes observations, visual analysis of literature studies, and interviews) and analytic descriptions. The theory utilized is an international organization and collective memory. The result of this study finds that UNESCO has four international organization roles which are mentioned as information, normative, operational, and rolesupervisory. The dominating function is the operational functions and is an actor to ask for collaboration. The collective memory finds that the manuscript of Negarakertagama is a genuine source of literacy regarding the history of the Majapahit Kingdom which is now safeguarded by the National Library of the Republic of Indonesia after survives the spoils of war with the help of Brandes, a Dutch philologist.